Unequal Risks: Ethnicity, Region, and Cybersecurity Outcomes in the United States (Journal of The Colloquium for Information Systems Security Education, 2026)
Cybersecurity risks are often treated as uniform, yet disparities across demographic groups suggest otherwise. This study investigates how ethnicity and geographic region shape cybersecurity outcomes in the United States, focusing on victimization, tool adoption, and awareness. Survey data from 470 adult participants were analyzed using ANOVA, Kruskal–Wallis tests, chi-square analyses, and logistic regression models. There are a few key findings. First, Asian/Pacific Islander respondents reported higher awareness and greater use of protective tools; they also faced significantly elevated odds of identity theft, phishing losses, and account takeovers. Second, suburban residents exhibited higher preparedness than urban or rural populations, while also consistently experiencing greater exposure to cyber incidents, particularly financial fraud. Finally, Hispanic/Latinx and rural groups reported lower adoption of security tools, reflecting barriers of access and language. These findings highlight that awareness and adoption alone are insufficient when structural vulnerabilities and targeted exploitation are at play. The study underscores the need for culturally competent education, expanded infrastructure access, and adaptive monitoring systems to reduce disparities and promote a more equitable cybersecurity landscape.
Keywords: cybersecurity disparities; demographic factors; cyber victimization; digital divide; ethnicity; regional differences